A Swat-Based Decision Support System for Multipurpose Reservoir Operation and Food-Water-Energy-Environment Trade-Off Analysis: Case Study of Selingue Reservoir - Sia, Edgard Tisson (Université d'Ottawa / University of Ottawa, 2023)
The world's water resources face unsustainable pressure from population growth, changes in consumption patterns, pollution, and overexploitation. Water resources managers have developed holistic approaches such as IWRM (Integrated Water Resources Management) and, more recently, the WEEF (Water-Energy-Environment-Food) nexus to address the situation. However, their application in day-to-day water resources management is still challenging due to the of little knowledge, data, and tools. One area where that challenge needs practical solutions is reservoir operation. The current study aims to improve the reservoir module in the Soil and Water Assessment Tool (SWAT) so that operation rules that aim to meet various water, food, and electricity objectives can be simulated. The improved SWAT model is used to simulate the management of the Sélingué reservoir in Mali, West Africa. The reservoir operation was simulated under three different operation rules: 1) priority to monthly hydropower production (HPP) target (rule 1); 2) respect of predefined monthly target storage (rule 2); 3) priority to downstream environmental flow, irrigation, and municipal water demands (rule 3). Results show that when priority is given to the HPP target (rule 1), 98.3% of the electricity demand is met. At the same time, the dam can supply 81.72% of the water demand to maintain environmental flow and sustain irrigation and municipal water consumption. It also ensures water availability with an annual target storage deviation estimated at 1.8%. When rule 2 is implemented, a gap of 8.5% between electricity production and electricity demand is observed. Rule 2 also failed to sustain environmental flow and supply flow for irrigation and municipal consumption as a gap of 15.39% between the supply and the demand was observed. Similarly to rule 1, It ensures water availability with an annual target storage deviation estimated at 1.25%. When rule 3 is enforced (i.e., the priority is given to environmental flow, irrigation, and municipal water demands) the reservoir can maintain the environmental flow and maintain irrigation, and municipal water requirements with a gap of 17.7% between the supply and the demands. However, HPP production decreases with a gap of 12.56% between the electricity supply and demand. Its capacity to supply water in the long term is low as it has the highest target storage deviation with a value of 18%. These results indicate that rule 1 offers more guarantees considering the food and electricity security and environmental challenges. Note that the simulations are done assuming that these rules are systematically followed. In practice, decision-makers can deviate from a rule in exceptional circumstances to maximize benefits or avert unwanted consequences. Finally, a decision support system (DSS) was developed to assist decision-makers in selecting efficient reservoir operation policies for multipurpose reservoirs combining HPP and irrigation.
Keywords: Reservoir operation; SWAT; DSS; Decision support system; Water; Food; Energy; Multiple purpose reservoir; Water management; Soil and water assessment tool